The Effect of Physical Education on Students' Mental Health - Hasanah, Azzahra Ushwatun; Rahmatullah, Muhammad Imam (Journal of Physical Education Innovation, 2024)
Mental health is an important aspect for students to support academic performance, productivity and overall well-being. However, various factors such as academic pressure, lifestyle changes, and lack of physical activity can have a negative impact on students' mental health. Physical education is considered an effective intervention to promote mental health among students through participation in physical activity and sports. This study aims to provide a more comprehensive understanding of the role of physical education in promoting mental health among students, by considering various aspects such as type of physical activity, frequency, intensity, and psychosocial factors involved. In this research, the approach used is a literature review or literature review. The research instrument used is a table of relevant research results to collect and analyze data from various literature sources related to the topic of the influence of physical education on students' mental health. The results showed that participation in physical education and physical activity had a positive impact on students' mental health, such as improving mood, reducing symptoms of depression and anxiety, and improving social functioning and interpersonal skills. However, there are significant differences in mental health status between men and women, with men tending to have better conditions. In conclusion, integrating physical education into the higher education curriculum to support students' mental well-being.